2015
DOI: 10.1039/c4dt03181d
|View full text |Cite
|
Sign up to set email alerts
|

Versatile properties of CaGd2ZnO5:Eu3+ nanophosphor: its compatibility for lighting and optical display applications

Abstract: Red color-emitting CaGd2ZnO5:Eu(3+) (CGZO:Eu(3+)) nanophosphors were synthesized by a facile sol-gel process. The structural and luminescent properties of these phosphors were investigated as a function of annealing temperature and Eu(3+) ion concentration. The orthorhombic phase was confirmed at different annealing temperatures, showing an irregular morphology within the nanoscale range. Photoluminescence (PL) excitation spectra of CGZO:Eu(3+) showed host absorption band (HAB), charge transfer band (CTB), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…It started to decrease from 1000 to 1400 °C because the formation of Zn2SiO4 started to collapse at higher temperatures in the ZnO-SiO2 composite. The absorption edges became smaller and, thus, decreased the optical band gap [32][33][34]. On the other hand, the obtained optical band gap value is in agreement with a previous study where pure SiO2 was used [35], which resulted in the band gap being indirect.…”
Section: Optical Studiessupporting
confidence: 91%
“…It started to decrease from 1000 to 1400 °C because the formation of Zn2SiO4 started to collapse at higher temperatures in the ZnO-SiO2 composite. The absorption edges became smaller and, thus, decreased the optical band gap [32][33][34]. On the other hand, the obtained optical band gap value is in agreement with a previous study where pure SiO2 was used [35], which resulted in the band gap being indirect.…”
Section: Optical Studiessupporting
confidence: 91%
“…Currently, commercial white LEDs (WLEDs) are mostly based on blue LEDs with YAG:Ce yellow phosphors as a color conversion layer (CCL) dispersing in the silicone or polymer matrix that are often used as packaging materials in the LED industry. However, there are certain disadvantages of phosphors like light blocking, leaking, , and even relatively low color quality, , and their poor compatibility with packaging resin, which were crucial factors in the application of WLEDs. On the other hand, these phosphors generally involve expensive rare earth ions that are resource-restricted and not environmentally friendly .…”
Section: Introductionmentioning
confidence: 99%
“…1(a) shows the XRD patterns of the CGZO:1Dy 3 þ nanophosphor annealed at 1200 ºC. According to our earlier reports [15,16], the optimal annealing temperature was found to be at 1200 ºC and the dilute concentrations of doping ions did not show any considerable effect on the crystallite size and phase purity [16]. Recently, Xu et al [17] reported the crystal structure of the novel CGZO host lattice, but the JCPDS card is not available till now.…”
Section: Resultsmentioning
confidence: 91%